2021
DOI: 10.1101/2021.08.19.21262323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Early Treatment with Fluvoxamine on Risk of Emergency Care and Hospitalization Among Patients with COVID-19: The TOGETHER Randomized Platform Clinical Trial

Abstract: BackgroundRecent evidence indicates a potential therapeutic role of fluvoxamine for COVID-19. In the TOGETHER randomized platform clinical trial for acutely symptomatic patients with COVID-19, we assessed the efficacy of fluvoxamine vs. placebo in preventing either extended emergency room observation or hospitalization due to COVID-19. Herein, we report the preliminary findings.MethodsThis placebo-controlled, randomized, adaptive, platform trial conducted among symptomatic Brazilian adults confirmed positive f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…A larger clinical trial on fluvoxamine was recently completed in Brazil led by investigators from Brazil and Canada (16). This study appears to support the value of fluvoxamine in early intervention in COVID-19 patients in preventing progression, serious complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A larger clinical trial on fluvoxamine was recently completed in Brazil led by investigators from Brazil and Canada (16). This study appears to support the value of fluvoxamine in early intervention in COVID-19 patients in preventing progression, serious complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…6 Finally, the preliminary results of the multicenter randomized placebo-controlled TOGETHER trial showed a significant and substantial reduction in risk of hospitalization or retention in a COVID-19 emergency setting due to COVID-19 associated with fluvoxamine use vs placebo in 1472 outpatients with COVID-19 who were at a high risk for developing severe complications. 7 Taken together, these convergent results from observational, preclinical, and clinical studies performed by different research teams call into question the mechanisms that underlie this potential positive effect of certain antidepressants against COVID-19. Several studies have led to a substantially improved understanding of those potential multiple and likely interrelated mechanisms.…”
mentioning
confidence: 99%
“… 60 Similarly, a study with 3238 Covid‐19 patients revealed a beneficial effect of the antidepressant fluvoxamine, reducing the need for emergency room observation or hospitalization. 61 A small randomized clinical trial with 152 COVID‐19 outpatients revealed a lower likelihood of clinical deterioration for patients receiving fluvoxamine. 62 Furthermore, a recent preclinical study found the antidepressant fluoxetine as an inhibitor of SARS‐CoV‐2 in human lung tissue.…”
Section: Antidepressantsmentioning
confidence: 99%